PENEGAKAN HUKUM TERHADAP PELAKSANAAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DI KECAMATAN RUMBAI KOTA PEKANBARU BERDASARKAN PERATURAN DAERAH PROVINSI RIAU NOMOR 6 TAHUN 2012 - Utama, Andrew Shandy (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2018)
Companies that carry out their business activities in the field of natural resources and / or fields related to natural resources must carry out social and environmental responsibilities. However, PT Riau Crumb Rubber Factory does not carry out corporate social responsibility in accordance with what is stipulated in the Riau Provincial Regulation Number 6 of 2012 to the people who live in the vicinity of the company area. The problem that will be discussed in this research is how is the law enforcement on the implementation of corporate social responsibility in the Rumbai Subdistrict of Pekanbaru City based on the Riau Provincial Regulation Number 6 of 2012? The research method used in this research is socio-legal research. The results of this research that if PT Riau Crumb Rubber Factory does not carry out corporate social responsibility to the community, then the company will be subjected to administrative sanctions by the Riau Provincial Government in the form of written warnings, restrictions on business activities, freezing of business activities, up to the revocation of PT Riau Crumb Rubber Factorys business activities.